Winding current calculation and harmonic analysis of controllable reactor of transformer type. Issue 1 (2nd January 2016) - Liu, Yi-bin; Tian, Ming-xing; Yin, Jian-ning
Abstract: The harmonic currents in each of the windings of controllable reactor of transformer type (CRT) have a close relationship with each of its thyristors' trigger angles. Based on the definition of the trigger angle vector, switching sequence and multi-winding regulation mode, the matrix expression for the windings' instantaneous current in the multi-winding regulation mode is obtained by means of subsection linearization; and then a simple method that can directly generate each winding's current waveform is presented. Using Fourier series, the functional relationship in matrix form between Fourier coefficients of all the windings' harmonic currents and the trigger angle vector is deduced, and then the formulae for calculating the root mean square (RMS) of each winding's harmonic current is acquired. The examples show that the proposed formulae for calculating the winding current of CRT and its harmonics in multi- winding regulation mode are correct, which can be used in more general cases, and the formula deduced in the single winding regulation mode described in other relevant literatures is merely a special case of this paper. This work expands the analysis methods of winding currents of CRT, and lays a theoretical foundation for the harmonic optimization and winding capacity configuration of CRT.